2011
DOI: 10.1002/ppap.201100128
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of U‐937 Monocytes on Different Amine‐functionalised Polymer Surfaces

Abstract: Human U‐937 monocytes are notoriously reluctant to adhere to normally cell‐adhering surfaces, for example tissue‐culture poly(styrene). In earlier work, these laboratories observed that organic thin films prepared by plasma‐ or ultraviolet‐assisted polymerisation, so‐called PVP:N, did facilitate the adhesion and proliferation of U‐937 under the condition that the concentration of primary amines exceed a critical value, [NH2]crit ≥ 4.2 at.%. That criterion being satisfied by pristine Parylene diX AM, we have co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 31 publications
1
41
1
Order By: Relevance
“…As discussed in detail elsewhere for the case of coatings containing N‐based functional groups, for example primary amines (CNH 2 ), chemical and physical stability (insolubility, foremost), are key attributes that plasma‐ or VUV‐deposited coatings must possess if they are to serve successfully in biotechnological contexts, for example in cell culture or tissue engineering . In the Introduction, we pointed out specific shortcomings of aminated films, namely the tendency of (CNH 2 ) groups to oxidize in the presence of atmospheric oxygen or water, thereby forming amides; furthermore, coatings containing high concentrations of hetero‐atoms, both N or O, tend to be quite soluble in polar solvents. In this latter regard, however, we earlier reported that UV‐PE:N tends to be less soluble in water that L‐PPE:N, for comparable [N] values .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed in detail elsewhere for the case of coatings containing N‐based functional groups, for example primary amines (CNH 2 ), chemical and physical stability (insolubility, foremost), are key attributes that plasma‐ or VUV‐deposited coatings must possess if they are to serve successfully in biotechnological contexts, for example in cell culture or tissue engineering . In the Introduction, we pointed out specific shortcomings of aminated films, namely the tendency of (CNH 2 ) groups to oxidize in the presence of atmospheric oxygen or water, thereby forming amides; furthermore, coatings containing high concentrations of hetero‐atoms, both N or O, tend to be quite soluble in polar solvents. In this latter regard, however, we earlier reported that UV‐PE:N tends to be less soluble in water that L‐PPE:N, for comparable [N] values .…”
Section: Resultsmentioning
confidence: 99%
“…In the Introduction, we pointed out specific shortcomings of aminated films, namely the tendency of (CNH 2 ) groups to oxidize in the presence of atmospheric oxygen or water, thereby forming amides; furthermore, coatings containing high concentrations of hetero‐atoms, both N or O, tend to be quite soluble in polar solvents. In this latter regard, however, we earlier reported that UV‐PE:N tends to be less soluble in water that L‐PPE:N, for comparable [N] values . Therefore, it has been of interest to confront UV‐PE:O and L‐PPE:O coatings in regards to their relative solubility, but also for possible compositional changes after exposure to O 2 or water, presuming that such coatings cannot undergo further oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is illustrated in Figure 1, where we note that the different surfaces have widely-varying values of "critical" total nitrogen concentrations, [N] crit , but the above-cited near-identical primary amine concentrations, [NH 2 ] crit . Since then, we have also examined a commercial coating, Parylene diX AM, aminomethyl- paracyclophane, and have found it to possess very similar characteristics [9]. In view of what is presented in the Introduction, one might speculate that attachment here may either be (a) purely "chemical" in nature, or (b) dictated by a primarily physical (electrostatic) effect.…”
Section: Resultsmentioning
confidence: 93%
“…Our previous work has revealed that nitrogen functional groups including primary, secondary, and tertiary amines possesses some capability to inhibit bacteria growth while promoting the growth and osteogenesis related marker expression of osteoblasts in contact [21,22]. It has also been reported that these amine groups facilitate adhesion of extracellular matrix related proteins fostering the adhesion and proliferation of cells such as osteoblasts, fibroblasts, and so on [23][24][25][26]. The objective of this work is to investigate whether simultaneous introduction of Ag and nitrogen functional groups can serve the dual purpose of enhancing the cytocompatibility and antibacterial characteristics of medical polyethylene (PE).…”
Section: Introductionmentioning
confidence: 98%